Critical incidents: the respiratory system. Issue 12 (December 2019) - Miles, Edward TC.; Cook, Tim M.
Abstract: Respiratory complications are expensive, not just in terms of the overall litigation burden faced by anaesthetists but also, and more importantly, the mortality and morbidity burden faced by our patients. Critical incidents arising in the respiratory system can cause rapid deterioration if left unchecked: trauma to airway structures can be debilitating or even life threatening; hypoxaemia may result in damage to other organ systems, most notably the brain. Each patient carries their own risk profile, as well as unique ideas, concerns and expectations of their anaesthetist. An understanding of the potential critical incidents that may befall the respiratory system, a patient-centred approach to discussing these risks, and familiarity with the procedures for mitigating harm are all necessary components of safe, effective practice in anaesthesia.